The Influence of GLP-1 Receptor Agonists on Wound Healing After Surgery: What Current Evidence Tells Us - Fengler, Karolina; Solecka, Katarzyna; Urbanik, Agata; Jakubowska, Olga; Kominiak, Dominika; Oćwieja, Zuzanna; Wyborska, Agata; Pietrzak, Kamila; Mińkowski, Mikołaj; Gascon Carreno, Marcel (Quality in Sport, 2026)
Glucagon-like peptide-1 receptor agonists (GLP-1 RAs) are among the fastest-growing classes of pharmacological agents used in the management of metabolic diseases. Initially developed for type 2 diabetes mellitus, their indications have expanded to include obesity treatment. Commonly used agents include liraglutide, semaglutide, dulaglutide, and exenatide. This review aims to evaluate current evidence on the impact of GLP-1 receptor agonists on postoperative wound healing and surgical complications, as well as to explore the underlying biological mechanisms. A literature search was conducted using PubMed and Google Scholar, focusing on recent review articles and original studies addressing both mechanistic and clinical aspects of wound healing. The available clinical data remain inconclusive. Evidence from general surgery, orthopedics, and chronic wound management suggests that GLP-1 RAs may exert beneficial effects on wound healing. In contrast, studies in plastic and reconstructive surgery indicate a potential association with delayed healing, wound dehiscence, and local complications. In conclusion, GLP-1 receptor agonists may modulate the wound healing process, with effects varying depending on clinical context. Their use may reduce complication risk in some settings but could impair tissue regeneration in others. Individualized perioperative management and further high-quality studies are required to establish their safety.